2014
DOI: 10.1039/c3ra46630b
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of anion exchange membranes used for hydrogen production by ultrapure water electrolysis

Abstract: Solid-state alkaline water electrolysis using a pure water feed offers several distinct advantages over liquid alkaline electrolyte water electrolysis and proton exchange membrane water electrolysis. These advantages include a larger array of electrocatalyst available for oxygen evolution, no electrolyte management, and the ability to apply differential pressure. To date, there have been only a handful of reports on solid-state alkaline water electrolyzers using anion exchange membranes (AEMs), and there have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
131
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 52 publications
1
131
2
Order By: Relevance
“…35% after holding the cell at a constant voltage of 0.55V for 12 hours. Fuel cell performance with SEBS-based AEMs resulted in peak power densities of 300 mW/cm 2 at 70 • C. Anion exchange membranes (AEMs) are a promising technology for alkaline membrane fuel cells (AMFCs), 1-6 redox flow batteries (RFBs), 7-13 alkaline water electrolyzers (AWEs) [14][15][16] and reverse electrodialysis (RED) cells. 17,18 The AEMs commonly reported in peer reviewed papers mostly contain quaternary ammonium fixed cation groups, mainly in the form of benzyl trimethylammonium cations.…”
mentioning
confidence: 99%
“…35% after holding the cell at a constant voltage of 0.55V for 12 hours. Fuel cell performance with SEBS-based AEMs resulted in peak power densities of 300 mW/cm 2 at 70 • C. Anion exchange membranes (AEMs) are a promising technology for alkaline membrane fuel cells (AMFCs), 1-6 redox flow batteries (RFBs), 7-13 alkaline water electrolyzers (AWEs) [14][15][16] and reverse electrodialysis (RED) cells. 17,18 The AEMs commonly reported in peer reviewed papers mostly contain quaternary ammonium fixed cation groups, mainly in the form of benzyl trimethylammonium cations.…”
mentioning
confidence: 99%
“…There is a growing interest in using anion exchange membranes (AEMs) as separators in alkaline membrane fuel cells (AMFCs) [1][2][3] and in other energy conversion and storage systems such as redox flow batteries (RFBs), [4][5][6] alkaline water electrolyzers (AWEs) [7][8][9] and reverse electrodialysis (RED) cells. 10 RFBs are promising candidates for large-scale energy storage systems since the capacity, power and energy density parameters can be designed independently and easily modified even after installation.…”
mentioning
confidence: 99%
“…[1][2][3] Operating in alkaline conditions presents distinct and attractive advantages to AMFCs and solid-state alkaline water electrolyzers, in comparison to acidic proton-exchange membrane fuel cells and water electrolyzers. Under alkaline conditions, it is possible to achieve faster oxygen reduction kinetics, more efficient water management, there is greater flexibility in the choice of fuels, and more importantly, presents the possibility of using nonprecious-metal electrocatalysts.…”
mentioning
confidence: 99%
“…We have adopted this method in our previous works. 2,3,[14][15][16][17]36,37 It has been suggested that using aliphatic pendant spacer chains results in several advantages, including the formation of a well-hydrated and percolating phase resulting in high ionic conductivity, and lowering of degradation rates due to the presence of benzyl carbons. 24,25 However, some of the reports attesting to these advantages are not entirely conclusive, as they do not contain all the experiments necessary to characterize the degradation of the AEMs.…”
mentioning
confidence: 99%